CONSTRUCTION OF VACUUM CIRCUIT-BREAKER FOR 7.2 KV - Hejduk, Artur (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The paper presents the construction of vacuum circuit-breaker 7.2 kV with electromagnetic independent drive for each pole. The drives of new construction are equipped with permanent magnets. Simulations and tests results are presented.